Over a million students use our free study notes to help them with their homework
First take (x+2)(x+3) and expand to get x2 +3x+2x+6, which can be simplified to equal x2+5x+6.Then mutiple x2+5x+6 by (x+5). This will give you x3+5x2Answered by Cora H. • Maths tutor2883 Views
In order to raise money, we need the average number of wins to be smaller than the average number of losses by at least a factor of 0.4.The average number of wins will be the number of games multipl...
Find the wage received from normal rate= 8x14=112. We then find the wage received from working overtime by finding the number of extra hours worked (12-8=4) multiplied by the overtime wage of (1½ x14= 1.2...
area of a circle = pi x radius^264pi/4 = 16piStudent must be aware of the equation for the area of a circle and that they must divide by 4 to get the answer here
30 days in November; (30 X 9.43) = 282.9p (2435 X 4.12) = 10032.2p (10032.2 + 282.9) = 10315.1p 5% in VAT so total price is 105% of 10032.2p Convert 105% to decimal; 1.05 (1.05 X 10315...
←
367
368
369
370
371
→
Internet Safety
Payment Security
Cyber
Essentials